Determinants of Road Traffic Accidents Among Motorcycle Riders In Four Selected Sub-Counties, Kitui County, Kenya - Mutinda FK; Juma J; Muchiri J; Kariuki P (Ibom Medical Journal)
Background: Over 50 million instances of serious injuries have been documented annually, while 1.2 million instances of mortality related to traffic accidents are disclosed around the world. This study aimed to establish the determinants of road traffic accidents among motorcycle riders in selected four Sub-counties in Kitui County, Kenya.